ATIM-14. RESULTS OF PHASE II CLINICAL TRIAL OF ONCOLYTIC HERPES VIRUS G47Δ IN PATIENTS WITH GLIOBLASTOMA. (11th November 2019) - Todo, Tomoki
Abstract: Genetically engineered, conditionally replicating herpes simplex viruses type 1 (HSV-1) are promising therapeutic agents for cancer. We have developed a triple-mutated, third-generation oncolytic HSV-1, G47∆, that exhibits enhanced replication capability in a variety of cancer, efficient induction of specific antitumor immunity, and high safety features. G47∆ also kills cancer stem cells very efficiently. The first-in-man, phase I-IIa study of G47∆ in recurrent glioblastoma patients was performed from 2009 to 2014 at the University of Tokyo, followed by phase II investigator-initiated clinical trial in patients with recurrent or residual glioblastoma from 2015 to test the efficacy. In this phase II, each patient received stereotactic injections with G47∆ into the tumor, repeatedly, but into different coordinates, every 4 weeks, for the maximum 6 times. A set dose of 1 x 10E9 pfu/dose was used. In most patients, G47∆ was given in addition to the maintenance chemotherapy using temozolomide. The primary endpoint was a 1-year survival rate. The repeated stereotactic injections were well tolerated. The interim analysis showed that the 1-year survival rate of 13 patients was 92.3%, which was significantly higher than 15%, the preset control value based on meta-analysis of historical data. The statistical significance was above the criteria of early termination, so this trial was terminated early and considered as the pivotal study for new drug application. Severe adverse events related to G47∆ were experienced by 2 patients only, both of which were grade 2 fever. Because G47∆ was designated as a 'Sakigake' breakthrough therapy drug by the Japanese government, and further as an orphan drug for malignant glioma, a fast-track drug approval is expected. G47∆ has proven safe even when injected repeatedly 6 times into the brain. The use of G47∆ may become a preferred treatment that potentially leads to a cure of malignant glioma in the near future.